If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5x = 5x + 9x Combine like terms: 2x + 5x = 7x 7x = 5x + 9x Combine like terms: 5x + 9x = 14x 7x = 14x Solving 7x = 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 7x + -14x = 14x + -14x Combine like terms: 7x + -14x = -7x -7x = 14x + -14x Combine like terms: 14x + -14x = 0 -7x = 0 Divide each side by '-7'. x = 0 Simplifying x = 0
| c^2-16c=0 | | X(y^7-6)+6(y^7-6)=0 | | 2(2n+1)= | | 6(1.3p-3)=2.p-5 | | -4(x-2)+5x=5-6 | | 3(x-2)=2(x+6) | | ln(6x+1)= | | -(36)=-0.025c | | (a-b)2-(a+b)2= | | t-5=19 | | 9a-5-8a=-3+2 | | 7(p+1)-13(p-2)=2(p-3)+11 | | 0.2=5y | | 5n-2=2n-14 | | 1x-11=5x+10 | | 7v= | | -0.08x+2=-0.4 | | 3x+12=6x-33 | | -0.6r=0.8 | | -6x-6x-6= | | z^5+z^4+2i*z+2i=0 | | 5(6x-3)= | | 8n+4=2n+34 | | 4.1x=15.17 | | (2+i)*(1+2i)=0 | | -(6x-w)+3(-6w+x)= | | x*3+4x=196 | | -5q+8=-6q-12 | | 1x+27x+8x=818004 | | (2x+1)(7x+5)=0 | | 4x^2-9+25y^2-20xy= | | 54=2w+2l |